Rethinking global poverty measurement - Khalid Abu-Ismail; Gihan Abou Taleb; Racha Ramadan (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction] From a money-metric perspective, poverty is a crystal-clear concept. A household is considered to be poor (poverty is typically estimated for households, not for individuals) if the total income or expenditure of its members lies below a specific threshold (referred to as the poverty line) which reflects the cost of meeting the family's basic food and non-food needs. Poverty can be thus be defined in terms of the monetary value required to attain a particular level of welfare. In a way, money is a proxy for some of the broader dimensions of poverty - for example, with sufficient financial resources, households and individuals can conceivably purchase better health care and better education for their children. However, they cannot easily improve their own education or job opportunities or access good and sufficient public services if they are not there to begin with. Therefore, while the `money-metric' indicator of poverty is a powerful tool to understand the scope of deprivation, it should, at the very least, be supplemented by other indicators of well-being. (...)
Keywords: 330